Long-term depression in the hippocampal CA1 area of aged rats, revisited: contribution of temporal constraints related to slice preparation. - Jean-marie Billard (PLoS ONE, 2010)
BACKGROUND: The effects of low-frequency conditioning stimulation (LFS, 900 pulses at 1 Hz) of glutamatergic afferents in CA1 hippocampal area using slices from two different strains of adult (3-5 month-old) and aged (23-27 month-old) rats were reinvestigated regarding the discrepancies in the literature concerning the expression of long-term depression (LTD) in the aging brain. METHODOLOGY/PRINCIPAL FINDINGS: N-methyl-D-aspartate receptor (NMDA-R) dependent LTD was examined in both adult (n = 21) and aged (n = 22) Sprague-Dawley rats. While equivalent amounts of LTD could be obtained in both ages, there was significant variability depending upon the time between the slices were made and when they were tested. LTD was not apparent if slices were tested within 3 hours of dissection. The amount of LTD increased over the next three hours but more in adult than in aged rats. This age-related impairment was abolished by exogenous d-serine, thus reflecting the reduced activation of the NMDA-R glycine-binding site by the endogenous agonist in aged rats. Then, the amount of LTD reached asymptote at 5-7 hours following dissection. Similar temporal profiles of LTD expression were seen in young and aged Wistar rats. CONCLUSIONS/SIGNIFICANCE: Taken together, these results sound a cautionary note regarding the existence of an experimental "window of opportunity" for studying the effects of aging on LTD expression in hippocampal slice preparation.